2021
DOI: 10.1002/asia.202100704
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Chemoselective Oxidation of 4‐Methylquinolines into Quinoline‐4‐Carbaldehydes

Abstract: A convenient protocol for the synthesis of quinoline‐4‐carbaldehydes via chemoselective oxidation of 4‐methylquinolines using hypervalent iodine(III) reagents as oxidant is described. This method highlights metal‐free and mild reaction conditions, nice yield, good functional group tolerance, and high chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Six compounds ( 3aa , 3r ′, 3s , 5s, 6r ′, 6s ) were evaluated for their inhibition of the cell TPC-1 viability in vitro by the CCK-8 assay (Scheme ). The test results showed that most of them have stronger in vitro growth inhibitory activities than cisplatin (IC 50 = 0.85 μM), with IC 50 values of 0.50, 0.27, 0.38, 0.31, 0.19, and 0.90 μM. In particular, 6r ′ performed far better than cisplatin, which will be contributed to future drug design due to the great antineoplastic potential exhibited in this skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…Six compounds ( 3aa , 3r ′, 3s , 5s, 6r ′, 6s ) were evaluated for their inhibition of the cell TPC-1 viability in vitro by the CCK-8 assay (Scheme ). The test results showed that most of them have stronger in vitro growth inhibitory activities than cisplatin (IC 50 = 0.85 μM), with IC 50 values of 0.50, 0.27, 0.38, 0.31, 0.19, and 0.90 μM. In particular, 6r ′ performed far better than cisplatin, which will be contributed to future drug design due to the great antineoplastic potential exhibited in this skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…65 A potential alternative approach could be based off of the work of Guo, who reported the use hypervalent iodine for the production of aldehydes from methylquinolines, proposed to occur through a dearomatization mechanism. 66 In the case of secondary carbons, acetoxylation was observed instead (Fig. 2d).…”
Section: Introductionmentioning
confidence: 94%
“…55 A potential alternative approach could be based off of the work of Guo, who reported the use hypervalent iodine for the production of aldehydes from methylquinolines, proposed to occur through a dearomatization mechanism. 56 In the case of secondary carbons, acetoxylation was observed instead (Fig. 2d).…”
mentioning
confidence: 94%